Borrowing from '5-6' Lenders: Examining the Link Between Street Vendors' Profiles and Informal Borrowing Practices - Labitad, Jessa B (Randwick International of Social Science Journal, 2025)
This study examined the borrowing practices of street vendors in the Cogon public market, Cagayan de Oro, Philippines, with a specific focus on their reliance on the informal "5-6" lending system. The research assesses the relationship between street vendors' profiles (such as age, sex, type of products sold, and estimated daily sales) and their borrowing practices, including loan amount, interest rates, payment schemes, and the frequency of reborrowing. Utilizing a cross-sectional quantitative design, data were collected from 251 street vendors engaged in "5-6" lending. Chi-square tests were used to analyze the associations between vendor profiles and borrowing practices. Results revealed that most street vendors borrowed small-scale loans of P5,001-P10,000 ($87.24-$174.45), often with high interest rates of 20% over a two-month period, paying daily, which created a continuous debt and reborrowing cycle. Significant associations were found between age, daily sales, and credit value, as well as between product type, sex, and the frequency of reborrowing. The study concludes that the informal lending system imposes substantial financial burdens on street vendors, particularly women and those selling fast-moving goods, contributing to a cycle of debt dependency.